2021
DOI: 10.1002/1878-0261.13122
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colorectal cancer and type 2 diabetes: prognostic and genetic interactions

Abstract: The present study was undertaken to analyze prognostic and genetic interactions between type 2 diabetes and metastatic colorectal cancer. Patients’ survival was depicted through the Kaplan–Meier product limit method. Prognostic factors were examined through the Cox proportional‐hazards regression model, and associations between diabetes and clinical‐pathologic variables were evaluated by the χ2 test. In total, 203 metastatic colorectal cancer patients were enrolled. Lymph nodes (P = 0.0004) and distant organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…These patients can present with high-risk pathological features, including T3 and T4 tumors, which were also observed. A recent study also pointed out this association between T2DM and metastases to lymph nodes (p < 0.01) [20].…”
Section: Discussionmentioning
confidence: 78%
“…These patients can present with high-risk pathological features, including T3 and T4 tumors, which were also observed. A recent study also pointed out this association between T2DM and metastases to lymph nodes (p < 0.01) [20].…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, we previously reported that certain genes associated with type 2 diabetes (T2D) may also play a role in the malignant phenotype of OMD in CRC [ 104 ]. In particular, some variants associated with T2D, such as HNF1A p.I27L, IDE3 p.T105A, IRS1 p.S892G, and INSR p.A2G, although considered benign, could influence the activity of related proteins.…”
Section: Biomarkers Of Omdmentioning
confidence: 99%
“…Existing evidences show disorders of glucose and lipids metabolism, such as diabetes and obesity, are critical promoters of tumor metastasis (8)(9)(10). Diabetes patients are always accompanied by excessive reactive oxygen species formation, chronic inflammation, and healing barrier, which contribute to its carcinogenicity (11)(12)(13). Interestingly, some anti-diabetic drugs possess anti-tumor effects, which implies hyperglycemia can accelerate tumor progression (14,15).…”
Section: Introductionmentioning
confidence: 99%